Pengabdian Kepada Masyarakat Internasional Pelatihan Santripreneur Bagi Santri Islamic Foundation Center Thailand - Sulistyowati, Raya; Wening Patmi Rahayu; Norida Canda Sakti; Farij Ibadil Maula; A’rasy Fahrullah; Angga Martha Mahendra; Amaliyah, Khoirotul; Maulia, Danis (Universitas Negeri Surabaya, 2025)
In the digital era, limited access to technology and entrepreneurship training is a major challenge for students in Thailand. This Community Service Program is designed to improve entrepreneurial skills based on Islamic values ​​for students at The Foundation Islamic Center of Thailand. This training is conducted through a collaboration between the Association of Public Sector Accounting Educators (APSAE) and various national universities. The methods used include several stages including approach, preparation, implementation, and evaluation. This program has succeeded in improving students' knowledge and skills in entrepreneurship, especially in the application of Islamic values ​​in business. Evaluation of the activity showed a significant increase in participants' understanding of the concept of entrepreneurship and the technical skills needed to compete in the digital era. This PKM program not only makes a real contribution to the development of the economy and education of students, but also offers a community service model that can be adopted in various other educational institutions with the potential to provide broad positive impacts. Keywords: entrepreneurship, islamic entrepreneurship, training, santripreneurship, digital marketing